2022
DOI: 10.3389/fpsyg.2022.875246
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Psychological Symptoms of Dementia as a Means of Communication: Considerations for Reducing Stigma and Promoting Person-Centered Care

Abstract: Dementia has rapidly become a major global health crisis. As the aging population continues to increase, the burden increases commensurately on both individual and societal levels. The behavioral and psychological symptoms of dementia (BPSD) are a prominent clinical feature of Alzheimer’s disease and related dementias (ADRD). BPSD represent a myriad of manifestations that can create significant challenges for persons living with dementia and their care providers. As such, BPSD can result in detriments to socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
(85 reference statements)
0
20
0
Order By: Relevance
“…Furthermore, the OFT showed that the infected mice had an obvious corner preference, which is related to increased anxiety. It has been reported that anxiety-like behavior is also common in AD patients [ 39 , 40 ]; meanwhile, the data from the MWMT revealed that TgCtwh6 infection damaged the mouse spatial memory retention and spatial learning. However, the infected mice had normal mobility, suggesting that T. gondii infection hardly affects motor function in mice [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the OFT showed that the infected mice had an obvious corner preference, which is related to increased anxiety. It has been reported that anxiety-like behavior is also common in AD patients [ 39 , 40 ]; meanwhile, the data from the MWMT revealed that TgCtwh6 infection damaged the mouse spatial memory retention and spatial learning. However, the infected mice had normal mobility, suggesting that T. gondii infection hardly affects motor function in mice [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Persons with dementia maintain gaze with their partners, retain emotional traces of film clips, and can have accentuated responses to social contagion (Fredericks et al, 2018). Additionally, though some brain networks deteriorate, those that become heightened can at times account for psychosocial changes (Cope et al, 2022; Warren, 2022). These networks correspond to heightened emotions and implicit memory and, when negative, are often mistaken for the behavioral and psychological symptoms of dementia, rather than meaningful attempts to communicate unmet needs (Warren, 2022).…”
Section: Memory Systems and Preserved Memory Abilities: Explicit And ...mentioning
confidence: 99%
“…Increases are expected globally as a result of population growth and aging, and cognitive decline warrants urgent attention from policymakers and governments (Carroll, 2019 ). Reportedly, 6.2 million Americans aged ≥65 years are diagnosed with Alzheimer's disease (AD), and 13.8 million Americans are expected to have AD by 2060 (Warren, 2022 ). Therefore, AD and cognitive decline are associated with a high socioeconomic burden in the United States (US), and the burden is expected to increase 2-fold to 3.3% of the population by 2060 (Matthews et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%